Prevalence and distribution of enamel defects and dental caries in a region with different concentrations of fluoride in drinking water in Sri Lanka - Ekanayake, L.; Hoek, Wim van der (2003)
AIMS: To assess the prevalence and distribution of developmental defects of enamel and caries in 14-year-old children who had been lifetime residents in a region with different concentrations of fluoride in drinking water in Sri Lanka.DESIGN: A cross-sectional survey. SETTING: Uda Walawe--a rural area in southern Sri Lanka where fluoride concentration in ground water is reported to be within the range of 0.05-6.10 mg/l. METHOD: A total of 518 children from six representative schools from this area were examined for developmental defects of enamel and dental caries using the modified DDE index and WHO criteria. The present analysis is limited to 486 children from whom drinking water samples were collected. RESULTS: Based on the fluoride concentration of the drinking water source the children were categorised into four groups: <0.3, 0.31-0.49, 0.5-0.7 and >0.7 mg/l. The prevalence of enamel defects ranged from 29-57% whilst 27-55% of children were affected by diffuse opacities in the four groups. Of the ten teeth examined, between 1.6-3.6 teeth per child were affected by enamel defects. Maxillary first premolars were the most commonly affected by diffuse opacities followed by the maxillary canines. Caries prevalence varied between 18-25% whilst the mean DMFT and DMFS values ranged from 0.29-0.54 and 0.45-0.67 respectively. Occlusal surfaces were the most affected by caries. CONCLUSIONS: The wide differences observed in the prevalence and severity of enamel defects indicate that there are variations in individual response to high fluoride levels in drinking water. It also demonstrates the need to ascertain the factors that could contribute to the prevalence and severity of enamel defects other than high fluoride levels in drinking water.